People participating in the 1986 y-Walk - Brock, Trish (photographer):::Creator::::::::::::
Negative shows a large group of men, women and children walking in downtown San Jose for the 1986 y-Walk. A few of the participants are carrying balloons. The photograph is taken from behind the group as they cross South San Pedro Street and walk past a place of business with a sign that reads: "Anna Maria's Mexican Deli." The deli also has a banner attached to the building. It reads: [Gr]and [Ope]ning.